The effects of UV photocatalytic ethylene removal on postharvest disease prevention, fruit physiology and storage environment - Fletcher, Alexander George Devlin (2019)
Ethylene, a naturally produced gaseous phytohormone, causes many detrimental effects during post-harvest fruit storage. A UV photocatalytic ethylene removal system, designed for use in post-harvest fruit and fresh produce storage and transport, was investigated to determine how it affects storage environment, fruit physiology and fruit resistance to various postharvest plant pathogens.